396 A Rare Encounter of "Forgotten Disease". (19th August 2022) - Sengupta, S; Bose, S
Abstract: With the advent and prompt use of antibiotics after throat infections, the rare entity of Necrobacillosis has almost disappeared in clinical practice. Here we present a case of a fit and well 27-year-old lady who was brought into A&E with septic shock, DIC and MODS after initial diagnosis of a sore throat 4 days ago which was treated by oral antibiotics. She was found to have bilateral patchy consolidations which later became necrotic cavities, empyema thoracis, peritonitis and abscess cavities in abdomen with evolving splenic abscess, prolonged QT and ectopics and type 2 respiratory failure. She was resuscitated, intubated, and transferred to the ICU. With an isolate of Fusobacterium necrophorum from blood culture Meropenem, clindamycin and metronidazole were started. However, over the next few days of treatment, lack of clinical response prompted antibiotics changing, and surgical drainage of abscesses in chest and abdomen. Eventually after a considerable period of abdominal abscess drainage and about 3 weeks of metronidazole and other antibiotics followed by Piperacillin and tazobactam for another 3 weeks the patient recovered from sepsis and was stepped down to ward. This case though rare is a good example of the benefits of surgical drainage and prolonged antibiotics for septic patients with collections. A rapid weaning only results in re-collection and clinical deterioration, or recurrent collection as happened to this patient. This is a rare case of Lemierre's syndrome which depicts the surgical difficulties faced due to recurrent abscess cavities formed in this condition.